Intelligent System of Relay Protection of Electrical Network 6-10 kV with the Implementation of Automatic Correction of the Operation Set Point - Shilin A.A.; Dement’ev S.S.; Dikarev P.V. (Problems of the Regional Energetics, 2023)
The purpose of the study is to develop the architecture and working algorithm of intelligent relay protection of an electrical network with an isolated neutral. “Intellectualization” of relay protection is necessary to increase its sensitivity and reliability. This problem is relevant due to the accident rate of overhead power lines and incorrect operation of traditional relays. This is due to the fact that the set point is not adjusted according to the deviation of the line parameters with changing environmental and load conditions. The purpose of the study is achieved by solving the following problems: the concept of supplementing an electronic relay with a mechanism for correcting the operation set point is proposed. The use of the digital shadow of the electrical network is substantiated. The digital shadow interrogates the sensor system. The advantage of using a digital shadow as part of relay protection has been proven. This allows emulating faults and estimating currents to correct the setpoint. The most significant result of the study is an example of the implementation of intelligent relay protection using a digital shadow in the form of an artificial neural network. The application of a neural network for approximating the current function of a two-phase short circuit is demonstrated. The significance of the results lies in the improvement of the sensitivity and selectivity of current protection due to the digital shadow for working out emergency modes. The convenience of operating and reproducing a digital shadow in the form of a neural network is noted.